The Listeners and Other Poems - De la Mare, Walter, 1873-1956 (Salt Lake City, UT : Project Gutenberg, 2007)
"The Listeners and Other Poems" by Walter De la Mare is a collection of poetry written in the early 20th century. The book captures a variety of themes, showcasing the author's affinity for nature, the supernatural, and the exploration of human emotions. De la Mare's work is often characterized by its whimsical and haunting qualities, inviting readers into a world where the ordinary becomes extraordinary. In this collection, readers will find a tapestry of poems that evoke a sense of nostalgia and introspection. The titular poem, "The Listeners," depicts a mysterious encounter at a lonely house, where a traveler seeks acknowledgment from phantoms that dwell within. Other poems, such as "Old Ben" and "The Ghost," reflect on themes of aging, solitude, and the passage of time, interweaving scenes from both the everyday and the ethereal. De la Mare's mastery of language and imagery paints vivid pictures, drawing the reader into contemplative moments that linger long after the final lines. Each poem stands as a doorway to deeper reflections on life, memory, and the unseen connections that bind us all. (This is an automatically generated summary.)
Release date is 2007-09-10
E-text prepared by Juliet Sutherland, storm, and the Project Gutenberg Online Distributed Proofreading Team
Keywords: Poetry